Acute pancreatitis in children: efficacy of computed tomography severity index in the assessment, management, and prediction of complications. Issue 4 (October 2018) - Khan, Rizwan A.; Wahab, Shagufta; Ghani, Imran
Abstract : Aim: The aim of the study was to describe the assessment and management aspects and the role of computed tomography severity index (CTSI) in children with acute pancreatitis. Materials and methods: All the children (⩽14 years) admitted to the pediatric surgery unit of our institution with acute pancreatitis from 2003 to 2014 were included. This retrospective analysis studied the demographic, clinical, diagnostic, and treatment aspects and the role of CTSI. Results: The male-to-female ratio out of a total of 45 patients studied was 4 : 1. The differences in mean leukocyte count, mean serum amylase, and mean serum lipase were not significant in children with different CTSI scores. The children with higher CTSI scores are more likely to have both early and late complications, need for intensive care, and overall longer hospital stay. Conclusion: CTSI plays an important role in early determination of the clinical severity, guiding the need for intensive care and in predicting the occurrence of early and late complications in children with acute pancreatitis.